ANALYSIS OF THE EFFECT OF SUPPLY CHAIN MANAGEMENT ON THE COMPETITIVENESS OF COASTAL FISHERMAN COMMUNITIES IN NORTH MINAHASA DISTRICT - Karuntu, Merlyn Mourah; Palandeng, Indrie Debbie; Rogi, Mirah (Archives of Business Research, 2021)
Supply Chain Management is an integrative method or approach to manage the flow of products, information, and money in an integrated manner that involves parties ranging from upstream to downstream consisting of suppliers, factories, distribution networks and logistics services. Supplier is one of the most important links in determining the quality of the product and the speed at which the product reaches the consumer. In the capture fisheries industry in North Sulawesi, the coastal fishing community in North Minahasa Regency is one of the spearheads of the success of the capture fisheries industry supply chain because it functions as a supplier to the fish processing industry in North Sulawesi. The purpose of this study was to analyze the influence of Supply Chain Management, namely the variables of technical and managerial assistance, information sharing, trust, long-term relationships, and process integration on the competitiveness of coastal fishing communities in North Minahasa Regency. This study uses a causal associative research type. The analytical method used is Multiple Linear Regression Analysis. The results showed that technical and managerial assistance, information sharing and trust had a significant effect on the competitiveness of coastal fishing communities in North Minahasa regency, while long-term relationship variables and process integration had no significant effect on the competitiveness of coastal fishing communities in North Minahasa Regency.